Analysis Of Customer Loyalty Which Is Formed by Service Quality Dimensions Using Reflective Indicators - Himawan, Erry (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The Alfamart minimarket in the city of Surabaya is the subject of this case study investigation. The reason behind the author's research was to investigate the impact of service quality aspects on customer loyalty through the use of reflecting indicators. 180 respondents provided the primary data, which was graded on a level 5 Likert scale. Subsequently, the statistical package program for social sciences, version 26, was used to process the data (SPSS 26). The author's hypothesis was tested at α 0.05 and is based on theories and other prior investigations. The data processing results indicate that the independent variables related to service quality have a significant impact on customer loyalty both partially and simultaneously (simultaneously), although the degree of correlation between the independent and dependent variables is either normal or moderate. It is also evident from the data processing findings that the reliability variable is the most dominating variable, with the independent variable contributing 75.5% to the dependent variable. The research's consequences may offer empirical support for the two categories of factors examined. Practically speaking, modern market business people can also utilize it as reference material.